Writing in more than one language at primary school: the added value of collaboration among pupils - Torri, Stefania (Formazione & insegnamento, 2020)
This contribution explores collaborative writing within an empirical study now in its data analysis phase. It concerns didactic interventions carried out at the A. Rosmini primary school in Bressanone (BZ) where pupils write in three languages (English, German and Italian) and where the use of collaboration is prevalent. The intention is to identify the characteristics and advantages of collaboration which help to strengthen pupils’ writing skills. After highlighting how collaborative writing complements a process-based approach and brings with it various advantages, such as how it is an instrument for linguistic refinement and has authoritative pedagogical reference matrices (Don Milani and Mario Lodi), some examples of the pupils’ verbal reasoning are taken into consideration. It is concluded that collaborative writing acts as a magnifying glass on the pupils’ work for the teacher, and for the pupil themselves as an instrument of democratic education, as well as an opportunity for authentic language learning and personal growth.